A novel three-dimensional dual-band balun with frequency-independent phase difference and complete ground. Issue 1 (2nd January 2016) - Yao, Lidan; Wu, Yongle; Jiao, Lingxiao; Liu, Yuanan
Abstract : A novel three-dimensional (3D) dual-band balun employing the double-sided parallel-strip line (DSPSL) with inherent impedance-transforming capability and complete ground is presented in this paper. The proposed balun is mainly composed of two mutually perpendicular printed circuit boards (PCBs), one of which is a horizontal feeding plane with a slender slot and the other of which is a mounted board vertical to the former. An unbalanced input port and two balanced output ports are totally located at the feeding plane. Utilising the configuration of DSPSL, two different dual-band impedance transformers of two sections are placed in the top and bottom layers of the vertical mounted board respectively. Thus, the transformers are applicable to transform impedances at two frequencies simultaneously. Furthermore, the 180° phase difference is frequency-independent, which facilitates the broadband operation. For verification, two numerical examples with different frequency ratios are designed and simulated, one of which is fabricated on a Rogers 4350B board. Both the simulated and measured results exhibit excellent performance and agree well with each other. In essence, this 3D balun is comprised of a single-layer planar circuit configuration. Consequently, owing to easy integration and low cost, it will be widely applied in the balanced radio frequency components.